Implementasi Program Keluarga Harapan (PKH) Di Kecamatan Besulutu, Kabupaten Konawe - Mandari, Aswart Pryatno; Sartono, Sartono; Jopang, Jopang (REZ PUBLICA, 2020)
The Family of Hope Program (PKH) is one of the social protection programs provided by the government to reach underprivileged people or people from lower economic classes. This program is realized by providing cash assistance to Very Poor Households (RTSM). The purpose of this study was to determine and describe how the implementation of the Family Hope Program (PKH) in Besulutu District, Konawe Regency. In this study, the authors used a qualitative approach. The qualitative approach aims to describe the empirical reality that exists in a phenomenon in detail and depth. This research was conducted in Besulutu District, Konawe Regency, Southeast Sulawesi. The type of research used is descriptive research. Descriptive research is research that seeks to describe solutions to existing problems based on data. In research on the implementation of the Family Hope Program in researchers using qualitative data analysis techniques, the following results were obtained, namely: 1) PKH implementation in Besulutu District has gone quite well, seen from the process of initial meeting activities, validation, assistance with disbursement of assistance, updating data, and verification of PKH participant commitments and the existence of clear and firm sanctions for KPMs who do not fulfill their commitments. 2) Factors Affecting the Implementation of the Family Hope Program in Besulutu District, namely: Communication, resources, disposition and bureaucratic structure.